2009
DOI: 10.1353/hpu.0.0100
|View full text |Cite
|
Sign up to set email alerts
|

Community Responses to Diabetes and Mental Health Care for the Uninsured Population in Michigan

Abstract: Objective To examine how the safety net in Michigan is responding to the health care needs of their uninsured population with diabetes and/or mental illness. Methods We used a multiple-site case study design. Data were collected through interviews of key informants in five Michigan communities. Analytic patterns and themes were identified, and compared across communities and by organizational type. Results Informants reported they are managing to meet the needs of uninsured diabetics but are having great d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Additionally, processes including referrals and care coordination are of poor quality in some communities. 73 Thus, safety nets are an important part of the health care system that helps, especially low-income uninsured patients, to have access to care. Studies have shown the effectiveness of safety net programs in diabetes care, and others have shown the need for improvement in safety net care.…”
Section: Safetynet In Diabetesmentioning
confidence: 99%
“…Additionally, processes including referrals and care coordination are of poor quality in some communities. 73 Thus, safety nets are an important part of the health care system that helps, especially low-income uninsured patients, to have access to care. Studies have shown the effectiveness of safety net programs in diabetes care, and others have shown the need for improvement in safety net care.…”
Section: Safetynet In Diabetesmentioning
confidence: 99%